Predictive value of amplitude-integrated EEG (aEEG) after rescue hypothermic neuroprotection for hypoxic ischemic encephalopathy: a meta-analysis - Chandrasekaran,M; Chaban,B; Montaldo,P; Thayyil,S (Journal of Perinatology, 2017)
Objective:Amplitude-integrated electroencephalography (aEEG) is a useful bedside tool in predicting the neurodevelopmental outcome after neonatal encephalopathy; however, the prognostic accuracy may be altered by rescue hypothermic neuroprotection. The objective of this study is to examine the prognostic accuracy of aEEG for predicting long-term neurodevelopmental outcomes in term newborn infants undergoing therapeutic hypothermia for neonatal encephalopathy.Study Design:We examined all studies (Medline, Cumulative Index to Nursing and Allied Health Literature and the Cochrane Library; 2000 to 2014) comparing aEEG (6, 24, 48 or 72 h) in term encephalopathic babies undergoing therapeutic hypothermia, with neurodevelopmental outcome at 1 year or more. We extracted individual patient data from the eligible studies to calculate prognostic indices with exact confidence intervals (CIs). We considered continuous normal voltage as normal aEEG pattern and discontinuous normal voltage, burst suppression, flat trace and persistently low voltage as abnormal, and defined adverse outcome as death or moderate/severe disability at 1 year.Results:We reviewed a total of 70 articles, 17 of which met the inclusion criteria. Eight studies were excluded and 9 studies (N=520) were included in the meta-analysis. The pooled sensitivity and specificity for an abnormal trace at 6 h of age to predict adverse outcome were 96% (95% CI 91 to 98%) and 39% (95% CI 32 to 46%). The diagnostic odds ratio of an abnormal trace was highest at 48 h (66.9 (95% CI 19.7, 227.2)).Conclusions:A persistantly abnormal aEEG at 48 h or more is associated with an adverse neurodevelopmal outcome. The positive prognostic value of 6 h aEEG is poor and good outcome may occur despite abnormal aEEG. Conversely, a normal 6 h aEEG has a good negative predictive value although do not exclude adverse outcomes.